The Most Archaic Ocean: Beyond the Bosphorus and the Strait of Sicily - Cerri, Giovanni (Peitho. Examina Antiqua, 2013)
From immemorial time, many Tyrrhenian places of ancient Sicily and Italy were identified (also by the local people) with the main stages of the return of Ulysses (Cyclopes, Aeolus, Circe, etc.). Some Hellenistic critics (for example Aristarchus and Polybius) assumed that it was from the various ancient and pre-Homeric myths that Homer drew inspiration, in the same way that he did with the myth of the Trojan War, which certainly occurred before him. Thus, the voyage of Ulysses, after his losing the course because of the storm at Cape Malea, had to be located in those sites. But how can one explain the fact that Homer places the voyage from Circe to the Hades over the Ocean? Is it only a pseudogeographic poetic touch, aimed to magnify the exploit? Crates of Mallus did not think so: in his opinion, only some of the numerous adventures had taken place in the Tyrrhenian Sea, whereas Homer had purposefully placed some other exactly on the Atlantic Ocean, beyond the Pillars of Hercules (the ancient name given to the Straits of Gibraltar). Whichever of the two models one chooses, the route of Ulysses seems to be completely unlikely, both from the point of view of objective reality and from the point of view of poetic imagination (if one desires to retain at least some plausibility). It appears to be a senseless coming and going that takes the shape of some sort of a labyrinth. Furthermore, the navigation times suggested by the text do not accord at all (even approximately) with the distances among the real sites. For this reason, Eratosthenes held that, from Cape Malea onwards, Ulysses switched from the real world to that of fantasy, or better still to the world of some narrative fable that does not heed geography at all. The modern critics are inclined to agree with him and this thesis is nowadays the most popular one. Yet, a very serious objection can be raised here: the myth and the epos (since the most archaic era), are strictly linked to the geography and the topography as well – they are radically refractory to a narrative fable that totally contradicts the then realities of time and space. Why should Ulysses plunge from Cape Malea onwards straight into the Neverland kingdom? If we combine Odyssey’s data with those we can reconstruct for the earliest form of the Argonautic saga (taking also into account the chronology of the Greek western colonization), then we get the solution that neither the ancient nor the modern critics have guessed correctly: up to around the middle of the 8th century B.C., the Greeks thought the Ocean to flow just after the Sicily Channel, essentially coinciding with the so-called Tyrrhenian Sea, still completely unknown at that time. This new perspective can well justify the objective disorder of Ulysses’ route. Above all, it also bears a deeper poetic sense: the Hero had the chance to know and to experience not only some far and exotic countries in general terms (as it can happen to any off-course sailor), but he also met the very boundaries of the surfacing lands and the rushing waters which encircle the terrestrial disc, bordering the external cosmic abyss. Ulysses came back home alive. He was able to tell the stories about the lands where no human being could ever sail. This borderline that geographically is clearly located marks at the same time the insurmountable chasm between the physical and the meta-physical world.